Cyprus : Assessment of Financial Sector Supervision and Regulation, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision, Insurance Supervision, and Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2006)
The report summarizes the assessment of Financial Sector Supervision and Regulation on Reports on the Observance of Standards and Codes (ROSC) on banking supervision, insurance supervision, and securities regulation of Cyprus. The report assesses that the financial system in Cyprus is in a process of reform generated by liberalization and regulation owing to accession to the European Union. The paper analyzes competency in the banking sector and technical supervisory rules, and assesses its strengths and vulnerabilities in the implementation of financial standards mainly in cross-border cooperation, information exchange, and consolidated supervision.